Tunneling properties versus electronic structures in Si/SiO2/Si junctions from first principles - Ko, Eunjung; Lee, Kwang-Ryeol; Choi, Hyoung Joon (AMER PHYSICAL SOC, 2013)
Using first-principles calculations, we study tunneling properties and electronic structures of Si(001)/SiO2/Si(001) junctions in a wide energy range covering the local energy gap in the SiO2 regions. We show that the tunneling spectra T (E) as functions of energy E have overall similarity to the projected densities of states (PDOS) at the centers of the SiO2 regions, but T (E) and PDOS have significant difference in their dependencies on the SiO2 thickness. From the energy dependencies of T (E) and PDOS, distinctive energy ranges are recognized in the valence and conduction bands, reflecting the local electronic structures in the SiO2 region induced from the Si regions. From the difference in the SiO2-thickness dependencies of T (E) and PDOS and from eigenchannel analysis, we find that the tunneling wave function inside the SiO2 region decreases with a decay rate which itself decreases as the tunneling distance increases, resulting in a smaller averaged decay rate per length for a thicker SiO2 region. These results provide a rich picture for the SiO2 barrier in the aspects of tunneling and local electronic structures, and a theoretical framework generally applicable to other tunneling barriers.